ANALISIS PENANGGALAN DALAN TRADISI BILANG-BILANG PERSPEKIF ILMU FALAK (STUDI KEARIFAN LOKAL MASYARAKAT DI KABUPATEN LUWU UTARA) - Tasya; Aisyah , Nur (HISABUNA: Jurnal Ilmu Falak, 2025)
The main issue explored in this research is how the dating system in the bilang-bilang tradition is understood from the perspective of ilm falak (Islamic astronomy), focusing on the local wisdom of the community in North Luwu Regency. This central issue is further examined through two main research questions: (1) How are good and bad days determined in the bilang-bilang tradition in North Luwu Regency? and (2) What is the relationship between the local wisdom in the bilang-bilang tradition and the principles of ilm falak in determining dates? This research is qualitative in nature, using both anthropological and astronomical approaches. Data collection methods include interviews, documentation, and observation. The techniques for data processing and analysis are carried out in three stages: data identification, data reduction, and editing. The results of the study reveal two key findings. First, the bilang-bilang tradition serves as a traditional calendar system used to determine auspicious and inauspicious times for conducting various significant activities, such as weddings, moving houses, starting new jobs, and even for daily routines. The determination of time in this tradition involves a combination of days of the week, the moon's position, and specific hours, a system known as patika. Second, this tradition fully aligns with religious teachings, as it does not contain elements of polytheism, does not lead to the worship of entities other than God, and does not replace obligatory religious practices. Therefore, the tradition should not be regarded as a deviation, but rather as a form of local wisdom that remains consistent with religious principles. The implications of this research are twofold. First, the bilang-bilang tradition can serve as a contextual learning resource in education and as a consideration for local governments in formulating policies for cultural preservation and the development of culture-based tourism. Second, the tradition has the potential to serve as a bridge between culture and religious teachings, as well as an educational tool to introduce the concept of Islamic astronomy in a contextual and relevant way for today's generation.